2015
DOI: 10.1007/978-3-319-13482-6_6
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Disorders as Vulnerability Factors for Nicotine Addiction: What Have We Learned from Animal Models?

Abstract: Epidemiological studies indicate a high prevalence of tobacco smoking in subjects with psychiatric disorders. Notably, there is a high prevalence of smoking among those with dependence to other substances, schizophrenia, mood, or anxiety disorders. It has been difficult to understand how these phenomena interact with clinical populations as it is unclear what preceded what in most of the studies. These comorbidities may be best understood by using experimental approaches in well-controlled conditions. Notably,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 99 publications
0
6
0
Order By: Relevance
“…The effects of acute nicotine exposure on anxiety-like behavior is highly dependent on the task, dose, timing of testing, sex, strain, age, and basal anxiety levels of the animals ( 353 , 354 ). In the EPM, acute or subchronic systemic nicotine was found anxiolytic in some studies ( 280 , 285 , 293 ), anxiogenic at both low and high doses in others ( 288 , 289 , 292 , 294 ), or to have no effects ( 288 ), in rats.…”
Section: Effects Of Nicotine On Cognitive and Affective Endophenotypementioning
confidence: 99%
“…The effects of acute nicotine exposure on anxiety-like behavior is highly dependent on the task, dose, timing of testing, sex, strain, age, and basal anxiety levels of the animals ( 353 , 354 ). In the EPM, acute or subchronic systemic nicotine was found anxiolytic in some studies ( 280 , 285 , 293 ), anxiogenic at both low and high doses in others ( 288 , 289 , 292 , 294 ), or to have no effects ( 288 ), in rats.…”
Section: Effects Of Nicotine On Cognitive and Affective Endophenotypementioning
confidence: 99%
“…Tobacco dependence in individuals diagnosed with schizophrenia is 3–4 times higher than that of the general population (Le Foll et al, 2015). Our laboratory and collaborators have published a series of studies over the past 25 years that have demonstrated that rats neonatally treated with quinpirole (NQ), a dopamine D 2 /D 3 agonist during postnatal days (P) 1–11, 1–21, or 11–21, display an increase in sensitivity of the dopamine D 2 receptor throughout the animal’s lifetime without an increase in receptor number (Kostrzewa, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Animal models are advantageous in studying the role of nicotine and other drugs in the development of anxiety‐related disorders and impaired social behaviors, although more research is necessary to demonstrate the mechanisms involved (Le Foll, Ng, Di Ciano, & Trigo, ). Behavioral measures established to model unconditioned anxiety include the light–dark emergence test (EM), the elevated plus‐maze (EPM) test, and the social interaction (SI) test (Arrant, Schramm‐Sapyta, & Kuhn, ; Crawley, ; File, Cheeta, & Kenny, ; Le Foll et al, ; Pellow, Chopin, File, & Briley, ).…”
Section: Introductionmentioning
confidence: 99%
“…Animal models are advantageous in studying the role of nicotine and other drugs in the development of anxiety‐related disorders and impaired social behaviors, although more research is necessary to demonstrate the mechanisms involved (Le Foll, Ng, Di Ciano, & Trigo, ). Behavioral measures established to model unconditioned anxiety include the light–dark emergence test (EM), the elevated plus‐maze (EPM) test, and the social interaction (SI) test (Arrant, Schramm‐Sapyta, & Kuhn, ; Crawley, ; File, Cheeta, & Kenny, ; Le Foll et al, ; Pellow, Chopin, File, & Briley, ). The emergence test assesses competing approach‐avoidance motivations and clinically effective anxiolytics significantly increase exploration of the open‐lit compartment whereas anxiogenics reduce exploration (Arrant et al, ; Chauoloff, Durand, & Mormede, ; Crawley, ; Merlo Pich & Samanin, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation